Biocontrol Mechanism of Bacillus subtilis C3 Against Bulb Rot Disease in Fritillaria taipaiensis P.Y.Li - Ku, Yongli; Yang, Nan; Pu, Peng; Mei, Xueli; Cao, Le; Yang, Xiangna; Cao, Cuiling (Frontiers in Microbiology, 2021)
In recent years, bulb rot disease of Fritillaria taipaiensis P.Y.Li has become one of the main diseases that seriously affect the yield and quality of Fritillaria. This study mainly explored the mechanism of action and effect of Bacillus subtilis C3 and its antimicrobial substances on bulb rot disease in Fritillaria and provides a basis for research on the prevention and control mechanisms of biocontrol bacteria in Chinese herbal medicine. This study first explored the biological characteristics of Bacillus subtilis C3, tested the inhibitory effects of C3 and its antimicrobial substances on the pathogen Fusarium by liquid coculture tests and plate tests, and, finally, verified the effect of C3 on bulb rot disease in Fritillaria by field experiments. The results showed that the bulb rot pathogen of Fritillaria was Fusarium oxysporum. B. subtilis C3 could inhibit the growth of the pathogenic Fusarium and mainly played an antimicrobial role by secreting paeonol, apocynin and oxalic acid. The mechanism of inhibition was destruction of the structural integrity of the mycelial cells of the pathogenic Fusarium, causing the mycelium to break and swell, the contents of the cells to leak out, and the chromatin to condense, leading to cell death. This study revealed the main mechanisms of B. subtilis C3 and showed bright application prospect in the Chinese herbal medicine industry.